Analysis and Selection of Step-Down Converter for PEM Electrolyzer Applications - Palma, L. (International Symposium on Power Electronics, Electrical Drives, Automation and Motion, 2024)
Green hydrogen is emerging as a relevant energy vector in the transition to a carbon-neutral future. For hydrogen to be considered "green", its production must be based on renewable sources such as photovoltaic (PV) or wind power and carried out in electrolyzers. The latter are electrochemical reactors that operate at low DC voltage and demand a high supply current, and therefore their integration with renewable energy sources requires the incorporation of DC-DC power converters. In addition, due to the operating characteristics of the electrolyzers, the DC-DC converters used must be able to guarantee low output current ripple and process power with high efficiency. For this reason, the use of modular structures to implement the DC-DC converter appears as an attractive alternative. Among the wide range of existing modular topologies, the interleaved buck converter (IBC) and the partial power converter (PPC) emerge as promising candidates for electrolyzer applications due to their remarkable performance in output voltage and current regulation, as well as power conversion efficiency. In this paper an evaluation and comparison of these two topologies is conducted, ultimately highlighting the higher energy efficiency of the PPC, albeit at the expense of higher output current ripple.